Avaliação da atividade fotocatalítica do óxido de cobre imobilizado em suporte magnético nanoestruturado - Santos, Lílian Cruz (Universidade Federal de São Carlos, 2015)
Contamination by dyes is one of the main problems related to water and environment pollution. In recent years, the search for new alternatives for the appropriate treatment of organic wastewater compounds has intensified. This study aims to evaluate the photocatalytic activity of copper oxide nanoparticles II (CuO), as well as obtaining nanostructured magnetic and porous media for the immobilization thereof. The CuO is a p-type semiconductor that acts as a sink photogenerated electrons. In this work, the CuO has been obtained by coprecipitation,hydro and solvothermal methods, with particles sizes of approximately 15 nm, 1 μm and 1 μm respectively. The materials' photocatalytic activity have been evaluated under excitation in the visible and ultraviolet regions. In all the cases, CuO proved to be efficient for the Rhodamine B color removal in the presence of hydrogen peroxide under visible light for 1 hour; reaching over 90% of color removal effectiveness. The main factor that makes impracticable the use of photocatalysts for water treatment on a large scale is the difficulty on recovering the active material. Thus, in this study, a magnetic scaffold composed of magnetite:hydroxyapatite has been developed. Magnetite provided magnetic activity to the medium, while the hydroxyapatite was used to provide sufficient porosity to the material in order to immobilize the CuO nanoparticles. In addition, the magnetite was protected of the oxidation process and consequent magnetic activity loss. The magnetite and hydroxyapatite have been obtained by chemical coprecipitation, presenting average particles sizes of 50 and 15 nm, respectively. The magnetite:hydroxyapatite magnetic scaffold presented the desired homogeneous chemical composition, indicating a successful synthesis. The magnetic photocatalyst has been obtained by CuO impregnation on the magnetic scaffold using an ultrasonic probe-type. The photocatalyst immobilized on magnetic scaffold proved to be efficient on the color removal of Rhodamine B dye, reaching the same efficacy than pure CuO. The immobilized photocatalyst remained efficient on color removal when re-used.
Evaluation of photocatalytic activity of copper oxide immobilized on nanostructured magnetic scaffold
Keywords: Óxido cúprico; Hidroxiapatita; Magnetita; Fotocatálise heterogênea; Suporte magnético; CIENCIAS EXATAS E DA TERRA::QUIMICA